Tritium retention characteristics of the dust in LHD after the deuterium plasma experiment - Teppei Otsuka; Yuya Ando; Miyuki Yajima; Gen Motojima; Suguru Masuzaki (Nuclear Materials and Energy)
Tritium (T) retention of the dust particles collected at ten toroidal sections of the Large Helical Device (LHD) after the 21st experimental campaign, in which deuterium (DD) plasma experiments were conducted, were evaluated by an enhanced full combustion method (EFCM), and their individual T retention was characterized by a tritium imaging plate technique (TIPT) in combination with a scanning electron microscopy (SEM-EDS). A new method of fixation and storage of the dust particles containing T, called the electroconductive Resin surface Embedding Method (eREM), was successfully demonstrated for T retention characterization of the individual dust particles.From the EFCM results, total T retention in dust particles collected from all toroidal sections of LHD after the 21st campaign was found to be several hundred MBq. Much higher T retention was found in the flaky C dust particles at the toroidal section with the open helical divertor than in the other closed helical divertor sections. T retention in dust particles at the section of W-coated C divertor tiles was lower than at the other sections of C divertor tiles. Zr-Ti-V dust particles originating from in-vessel getter pump materials were found, and T retention in these particles was much lower than in the C dust particles.The results from TIPT in combination with SEM-EDS indicated not all the dust particles but a half of the dust particles retained T. Such the T retention characteristics of the dust particles could be attributed to T retention characteristics of the dust source resulting in the dust particles produced and transported, and the other is depth distribution of T in the individual dust particle thicker than T β-electron escaping range.